The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1007/bf01808762
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery with the first Austrian cobalt-60 Gamma-unit

Abstract: During the period of one year, from the 21. 4. 1992 to 21. 4. 1993, a total of 201 radiosurgical sessions on 181 patients were performed with the first Austrian Gamma-unit in Graz. 42% of radiosurgical sessions were undertaken for malignomas, 20% for meningiomas, 11.5% for vascular malformations, 9% for neurinomas, 8.5% for low grade astrocytomas and glomus jugulare tumours, 5% for sellar and suprasellar lesions, and 4% for functional disorders. Dose plan data for all the lesions treated are shown. Clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Using this method, 47 studies were initially identified (Fig. 1) (3, 4, 7–51). From this pool, 20 reviews or off-topic studies were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Using this method, 47 studies were initially identified (Fig. 1) (3, 4, 7–51). From this pool, 20 reviews or off-topic studies were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…While conventionally fractionated radiation therapy has a longer history in GJT management, inclusion of SRS in the therapeutic armamentarium dates back to mid-1990s [27,28]. Thus, nearly 2 decades of experience with GJT radiosurgery is currently available.…”
Section: Practice Pointsmentioning
confidence: 99%
“…While SRS techniques are currently capable of utilizing different types of radiation including heavy charged particles and protons, photon irradiation is more commonly used partly due to widespread availability with easier access and lower cost. Major platforms for GJT radiosurgery include the Gamma knife, Cyber knife and other LINAC-based systems all of which have been shown to achieve favorable treatment outcomes [21][22][23][24]27,28,30,. The recognition of SRS as a viable treatment modality has prompted continual development of novel technologies providing higher speed, comfort and precision.…”
Section: Practice Pointsmentioning
confidence: 99%
“…[28] Many meningiomas treated with radiosurgery have shown a reduction in tumor volume. [11,18,19,28,37] Several short-term reports have stated, in general, that radiosurgical treatment of meningiomas is safe and well tolerated. [19,20,26,28] Most of these data come from Lunsford's group at University of Pittsburgh, which was the site of the first North American gamma knife unit.…”
Section: Radiosurgical Treatmentmentioning
confidence: 99%